Detection of Hb Rothschild HBB: c.[112T>A or 112T>C], Through High Index of Suspicion on Abnormal Pulse Oximetry. (4th March 2017) - Alli, Nazeer A.; Wessels, Piet; Rampersad, Narisha; Clark, Barnaby E.; Thein, Swee Lay
Abstract: We describe a case with a low oxygen affinity hemoglobin (Hb) variant who presented with cyanosis in the absence of cardiopulmonary disease. The patient, a 27-year-old pregnant female (P1G2), complained of a productive cough and bluish discoloration of the lips that started 3 days prior to seeking attention. She had no previous episodes and has generally been in good health. A positive family history of cyanosis was obtained in one sibling. Systematic examination, notably the cardiorespiratory system, revealed no abnormalities. The arterial Hb oxygen saturation (SpO2 ) on pulse oximetry was 81.0% and Hb separation studies revealed an Hb variant identified as Hb Rothschild [β37(C3)Trp→Arg] ( HBB : c.[112 T>A or 112 T>C]) by gene sequencing. The amino acid substitution (Trp→Arg) is an important contact point at the α1β2 interface and favors a T-quaternary state of the Hb tetramer. This leads to a low oxygen affinity state, which results in premature release of oxygen and drop in oxygen saturation. In the absence of cardiopulmonary disease, a decreased oxygen saturation reading, with or without cyanosis, should arouse suspicion for a possible dysHb.